Mimetic desire and liberation in the victim’s intelligence (2020)
One of the intentions proposed by this work is to generate a philosophical reflection on the social definition of the victim. The hypothesis of this investigation is a hermeneutic approach on the ways that the philosophy of law has to reach the epistemic condition of the victim. By epistemic condition we understand the criteria of the possibility in which we can name the singularities of a social phenomenon, inevitably shown in the consciousness in an equivocal and elusive way. That is why, among the epistemological criteria that allows a real and existential approach to the object-subject of research, emanate from the sources of the mimetic theory of desire formulated by the thinker René Girard (1923-2015), and the thesis on political philosophy exposed by the Latin American philosopher Enrique Dussel (1934).